The role of the Uzbek stock market in the global market - Alikulov Azamat Tuygunovich, (THE INNOVATION ECONOMY, 2026)
The article is devoted to analyzing the dynamics of Uzbekistan’s stock market in 2020–2024 and its comparison with international experience. Despite the growth of capitalization and its ratio to GDP, a decline in the number of listed companies is observed. A comparative analysis with the USA, Japan, Korea, Russia, Kazakhstan, and other countries has revealed the strengths and weaknesses of the national market. In addition, the problems of a narrow investor base, insufficient corporate governance, and infrastructural limitations are highlighted. The conclusion provides recommendations for market development, including accelerating IPO and privatization processes, expanding the participation of institutional investors, and improving electronic trading systems and corporate governance standards.